The Role of Islamic Financial Institutions: Maintaining Market Integration and Preventing Distortion - Siregar, Tetty Handayani; Harahap, Isnaini; Ridwan, Muhammad (Danadyaksa: Post Modern Economy Journal, 2025)
This study analyzes how Islamic financial institutions can encourage inclusive economic growth, reduce social inequality, and create added value for all stakeholders. In this study, researchers used a descriptive qualitative method. The data source used library research, drawing from various scholarly materials such as books, peer-reviewed journals, and official reports. These sources were carefully selected based on their relevance and credibility, and the data was analyzed through thematic analysis to identify key insights and patterns. The results of the study showed that price distortions were caused by several factors including cartels and trader associations, which manipulate supply and pricing; ikhtikar (hoarding of goods to drive up prices); talaqqi ruqban (intercepting rural sellers before they reach the market to buy goods at unfair prices); tadlis (concealment of product defects); taghrir (misleading information to deceive buyers); and bay najasy (artificial price inflation through false bidding). Islamic financial institutions have a strategic role in preventing market distortions caused by usury practices by offering Sharia-compliant financial products that emphasize profit-and-loss sharing, ethical investment, and risk-sharing. Empirical evidence from studies on Islamic finance shows that these mechanisms contribute to price stability and more equitable wealth distribution. Islamic financial institutions can encourage sustainable economic growth without harming any party by implementing a fair and transparent profit-sharing system. However, to achieve this goal, government support is needed in the form of conducive regulations and comprehensive public education campaigns. These campaigns should focus on raising awareness about the principles and benefits of Islamic financial practices, promoting ethical market behavior, and providing training programs for market participants to ensure proper implementation of Shariah-compliant transactions.